Guidelines for Assessing and Enhancing the Organizational Vitality of Pharmacy Educational Programs: A Call to Action! - Ashim Malhotra; Jeremy Hughes; David G. Fuentes (MDPI AG, 2022)
Organizational vitality encompasses organizational mission and identity, organizational purpose and values, and employee engagement, cohesiveness, anxiety, and information sharing. Using the organizational vitality framework consisting of the following five pillars: (1) human, (2) knowledge, (3) intellectual, (4) financial capital, and (5) market value, we propose a reflection guide and specific calls to action for academic leaders including deans, department chairs, assistant/associate deans, and others within pharmacy and healthcare education systems. Our overall aim is to provide a blueprint for academic leaders to assess and enhance the organizational health, vitality, resiliency, and sustainability of their pharmacy educational programs using an established organizational vitality framework. This guide can help academic leaders at all levels to reflect on their organization's vitality and use the steps outlined here to renew conversations about faculty life, identities as leaders, the global pharmacy Academy's core mission and values, and the pursuit of work-life harmony in the context of their pharmacy schools' organizational vitality. All leaders within pharmacy educational programs should identify and embrace a holistic and guided framework that emphasizes organizational vitality.